Urban freight logistics and land use planning education: Trends and gaps through the lens of literature. (January 2023) - Baker, Douglas; Briant, Sarah; Hajirasouli, Aso; Yigitcanlar, Tan; Paz, Alexander; Bhaskar, Ashish; Corry, Paul; Whelan, Karen; Donehue, Paul; Parsons, Hermione
Highlights: Urban freight logistics is an understudied area of research with limited literature coverage. Urban freight logistics education is even much scarcely covered in the academic literature. Educational pedagogies are falling behind in meeting the skilled professional needs. Pedagogies are unable to support efficient, effective, and sustainable industry performance. Development of contemporary urban freight logistics education has utmost importance. Abstract: Supply chains, urban freight logistics and freight transport have been under pressure to improve productivity, quality, and sustainability performance. Conventional methods of practice are unable to respond to this industry's ever-growing challenges and needs. New methods/technologies have emerged to respond to this issue, making urban freight logistics a more contemporary, interdisciplinary and technology integrated field. Nevertheless, the application of new methods/technologies, and developments in the field are not fully integrated into training/education programs. This study utilised a systematic literature review along with thematic and content analyses to interrogate and explore the developments within urban freight logistics practises and compared them with the current developments in the literature on freight logistics training/education programs—to identify the gaps and limitations within the body of knowledge. The findings reveal that the literature on urban freight logistics education is lacking in terms of providing a comprehensive education on the spatial systems of moving freight in urban areas and is falling behind the current developments within the industry. This study highlights that there is a substantial gap in the body of knowledge on urban freight logistics education, given that many of the current studies in the literature are focus on freight logistics as a topic with no/limited consideration to the rapidly changing urban context.